Toward National Unified Medical Records (NUMR) and the Application of Nationwide Disease Registry - Harbi, Alya (2021)
Technology in healthcare has evolved, however, till this date many healthcare providers find it difficult to provide their services as intended as a result of fragmented systems and scattered data. The challenges are noticeable especially with the rapid population growth which demanded software engineering and state of art solution to be able to handle different constraints. Although couple of countries started to implement nationwide electronic systems that are interoperable, none have completely finalized the program yet. United Arab Emirates (UAE) started toward this initiative to integrate the different systems in healthcare whether public or private. In addition to that, managing the burden of diseases is becoming uncontrollable and National Unified Medical Record (NUMR) is a starting point toward proper management to raise the healthcare quality and cut the cost. The aim of this study is to set new directions toward establishing NUMR and its applications of nationwide disease registry and assess the current situations and needs to be able to establish a proper mechanism and standards for UAE and other countries to benefits from, as well as study the application of disease registry and how we can utilize the concept of data mining, and business intelligence for better nationwide population management. Having NUMR will facilitate having proper nationwide disease registry that would enable analytics and prediction for better management. This study will bring great benefits for all countries that are going toward nationwide and interoperable healthcare platform. Moreover, it should be mentioned that there are limited nationwide disease registries worldwide especially for cardiology and diabetes, making it difficult to strategize the prevention programs in these field. Hence, it is very crucial to study the standards and mechanisms with respect to this field in order to provide lessons learned from other countries having a similar direction. The future of implementation of NUMR in UAE is promising. Our findings offer beneficial guidelines for consideration in implementing NUMR system across UAE and also help in the drive to improve healthcare systems nationally.